Wasl al-fiqh bi al-Hadith: Pelaksanaan di Dayah Tradisional Aceh / Lazuardi Muhammad Latif - Lazuardi , Muhammad Latif (2021)
Wasl al-Fiqh bi al-lfadith is a concept which integrates the study of jurisprudence and hadith so that fuqaha' will have access to better guidance in formulating their rulings. The concept will also help the muhaddithiun in deriving a more accurate interpretation of the hadith they study. Traditional dayah is the oldest Islamic educational institution in the Malay Archipelago, which is highly respectable among the people of Aceh and is often relied upon for religious rulings and Islamic teachings. This study, which was a field study, took place at Dayah Mudi Mesra, Samalanga, Aceh. It was selected as the site of the study due to its long-established reputation and great influence among the people of Aceh. The study was carried out to shed some light on the concept of Wasl al-Fiqh bi al-Hadith as discussed by Islamic scholars throughout the history of Islamic law, analyze the challenge of traditional dayah in implementing the concept of Wasl al-Fiqh bi al-lfad/ih, analyze the role of Dayah Mudi Mesra in implementing the concept of Wasl al-Fiqh bi al-Hadith, and analyze the detailed aspects of its implementation and implications for the students and its alumni. The study employs a mixed method, combining qualitative and quantitative data collection instruments consisting of library data, interviews, questionnaires, observations, and documentation. Inductive, deductive, and comparative methods were used for data analysis. The study found, according to some historical accounts, that the concept of Wasl al-Fiqh bi al Hadith is actually a method to reinforce the use of hadith as the second source of law from which fiqh is derived. Overall, traditional dayah in Aceh still face challenges in combining the teaching of fiqh and hadith. Dayah Mudi Mesra, in particular, has not assumed a pivotal role in carrying out the task as it should have. The study also found that the implementation of this concept at dayah has been synonymous to the exclusive adoption of the mazhab of al-Shafi'i as learned from a number of Shafi' i books or as taught by some Shafi' i scholars as a primary reference. This has led to some negative implications both in the socio··religious aspect, such as the emergence of ghuluww in specific religious practices and the rejection of any possible differing\ opinions, and in the socio-political aspect, such as efforts to influence government officials or government policies and to take control of government's strategic positions in order to legitimatize certain religious practices and to force people into subscribing to such practices.